A multinational cohort study examining sex differences in excess risk of death with graft function after kidney transplant - Vinson, Amanda Jean; Zhang, Xun; Dahhou, Mourad; Süsal, Caner; Döhler, Bernd; Sapir-Pichhadze, Ruth; Cardinal, Heloise; Melk, Anette; Wong, Germaine; Francis, Anna; Pilmore, Helen; Foster, Bethany J. (Transplantation, 2024)
Background: Kidney transplant recipients show sex differences in excess overall mortality risk that vary by donor sex and recipient age. However, whether the excess risk of death with graft function (DWGF) differs by recipient sex is unknown. - Methods: In this study, we combined data from 3 of the largest transplant registries worldwide (Scientific Registry of Transplant Recipient, Australia and New Zealand Dialysis and Transplant Registry, and Collaborative Transplant Study) using individual patient data meta-analysis to compare the excess risk of DWGF between male and female recipients of a first deceased donor kidney transplant (1988-2019), conditional on donor sex and recipient age. - Results: Among 463 895 individuals examined, when the donor was male, female recipients aged 0 to 12 y experienced a higher excess risk of DWGF than male recipients (relative excess risk 1.68; 95% confidence interval, 1.24-2.29); there were no significant differences in other age intervals or at any age when the donor was female. There was no statistically significant between-cohort heterogeneity. - Conclusions: Given the lack of sex differences in the excess risk of DWGF (other than in prepubertal recipients of a male donor kidney) and the known greater excess overall mortality risk for female recipients compared with male recipients in the setting of a male donor, future study is required to characterize potential sex-specific causes of death after graft loss.
Gesehen am 18.08.2025